A Systematic Review of Research Trends in Cooperative Learning Models in Science Learning - Isniwana Damayanti; Inayatil Baqy; Joni Rokhmat (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2025)
This study aims to systematically review trends, patterns, and thematic developments in research related to cooperative learning models in science education. Utilizing a descriptive-analytical method, data were collected from documents indexed in Google Scholar, published between 2016 and 2025. The data were analyzed using bibliometric tools, including Publish or Perish, VOSviewer, and Dimensions.ai. The analysis highlights several key aspects, including publication trends, types of sources, top-cited articles, disciplinary research categories, and keyword mapping. Findings indicate a significant increase in research interest, particularly after 2021, with dominant focuses on improving students’ motivation, learning outcomes, and scientific literacy. Cooperative learning models such as STAD, Jigsaw, TGT, TPS, and TSTS were the most frequently studied. The keyword analysis revealed six thematic clusters emphasizing cognitive, motivational, collaborative, and communicative dimensions of cooperative learning. This review underscores the growing significance of cooperative learning in 21st-century science education and identifies gaps for future research.